2017
DOI: 10.1038/ejcn.2017.76
|View full text |Cite
|
Sign up to set email alerts
|

Soyfood and isoflavone intake and risk of type 2 diabetes in Vietnamese adults

Abstract: Soyfood and isoflavone intake was associated with a lower type 2 diabetes risk in Vietnamese adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…Beside this, improvement in lipid profile, kidney function, endothelial function, and blood pressures has also been observed among the population supplemented with soybean isoflavones . A case–control study among Vietnamese adults (aged 40–45 years) showed that dietary intake of daidzein was significantly lower among diabetic population compared to controls and it was also associated with reduced risk of T2D . Similarly, Ho et al reported that supplementation with soy isoflavone containing 46.4% daidzein have a favorable effect on lowering fasting glucose in postmenopausal Chinese women.…”
Section: Effect Of Daidzein On T2d Pathophysiologymentioning
confidence: 97%
“…Beside this, improvement in lipid profile, kidney function, endothelial function, and blood pressures has also been observed among the population supplemented with soybean isoflavones . A case–control study among Vietnamese adults (aged 40–45 years) showed that dietary intake of daidzein was significantly lower among diabetic population compared to controls and it was also associated with reduced risk of T2D . Similarly, Ho et al reported that supplementation with soy isoflavone containing 46.4% daidzein have a favorable effect on lowering fasting glucose in postmenopausal Chinese women.…”
Section: Effect Of Daidzein On T2d Pathophysiologymentioning
confidence: 97%
“…However, when stratified by equol-producing status in women, genistein was protective only among equol producers and in men isoflavones concentrations were not associated with risk of DM, regardless of equolproducing status. In Vietnam, a hospital-based case-control study involving 599 newly diagnosed diabetic cases (age 40-65 years) and 599 hospital-based controls found higher intake of total soyfoods was significantly associated with a lower risk of DM [25] The adjusted OR for the highest versus the lowest intake was 0.31 (95% CI: 0.21, 0.46; P<0.001). An inverse dose-response relationship of similar magnitude was also observed for total isoflavones intake (OR: 0.35; 95% CI: 0.24, 0.49; p<0.001).…”
Section: Soy/isoflavone Exposure and Risk Of Diabetes: Epidemiologymentioning
confidence: 99%
“…Finally, there are two case control studies, one from Korea [24] and one from Vietnam [25], both of which provide some support for the protective effects of soyfoods, but the former comes with an important caveat. A nested case-control study comprised of 693 cases (316 women and 377 men) and 698 matched controls (317 women and 381 men) within the Korean Genome and Epidemiology Study found that in women, compared with the lowest quartile of plasma concentration of genistein, the highest quartile exhibited a significantly decreased risk of DM (OR 0.58, 95% CI: 0.35, 0.95) [24].…”
Section: Soy/isoflavone Exposure and Risk Of Diabetes: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Supplementation of soy protein more than 6 months significantly reduces Fasting Plasma Glucose, LDL-Cholesterol in T2DM and metabolic syndrome (Zhang et al, 2016). High intake of soybeans and isoflavones can reduce the risk of lower type 2 diabetes in Vietnamese adults (Nguyen et al, 2017). Administration of 15g of soy protein with 66mg of isoflavones improved significant glycemic control compared to 15g of soy protein without isoflavones (Sathyapalan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%